Analisis Pengaruh Program CSR PT. Indonesia Asahan Aluminium (PERSERO) dalam Meningkatkan Kesejahteraan Masyarakat Kabupaten Batu Bara, Sumatera Utara - Suci Etri Jayanti S; Rusmewahni Rusmewahni (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
The purpose of this study was to determine the impact of the Corporate Social Responsibility Program of PT. Indonesia Asahan Aluminum towards the welfare of the people of Batu Bara Regency. The variables in this research consist of Corporate Social Responsibility and Community Welfare. This research was conducted on the people of Sei Suka Subdistrict, Batu Bara Regency as many as 56,078 people, based on the slovin formula, 100 respondents were obtained as samples. The method in this research is descriptive quantitative using instruments in the form of a questionnaire / questionnaire, observation and interviews with Likert scale measurements. From the results of Simple Linear Regression Analysis, it shows that Corporate Social Responsibility (CSR) has a positive effect on Community Welfare. Based on the Coefficient of Determination Test, the R value states that the adjusted R value is 35.9%, which means that the welfare of the community is influenced by Corporate Social Responsibility (CSR), while the remaining 63.1% is influenced by other variables not examined in this study. From the results of the partial analysis (t test), the independent variable Corporate Social Responsibility (CSR) has a significant effect on the dependent variable, namely Community Welfare. This can be seen in the Coefficient table through hypothesis testing, it can be seen that the calculation results partially have a significant and significant effect on the Community Welfare variable.